2018
DOI: 10.1371/journal.pone.0204327
|View full text |Cite
|
Sign up to set email alerts
|

Complications associated with adolescent childbearing in Sub-Saharan Africa: A systematic literature review and meta-analysis

Abstract: ObjectiveTo examine whether childbearing before age 18 in Sub-Saharan Africa is associated with increased risk of maternal and child complications through a systematic literature review and meta-analysis.MethodsThe literature on adolescent pregnancy and associated complications in Sub-Saharan Africa was reviewed. A systematic electronic database search in Medline and Embase identified relevant papers. Studies were eligible for inclusion if they had numeric data on maternal mortality, pre-eclampsia, eclampsia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(122 citation statements)
references
References 33 publications
4
101
0
1
Order By: Relevance
“…Globally, pregnancy and childbirth complications are one of the leading causes of death among adolescent girls. Adolescent mothers face an increased risk of perinatal morbidities such as eclampsia, puerperal endometritis, systemic infections, low birth weight, preterm delivery, and severe neonatal conditions [10][11][12]. Indeed, early adolescent pregnancy has been linked with an increased risk of HIV infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, pregnancy and childbirth complications are one of the leading causes of death among adolescent girls. Adolescent mothers face an increased risk of perinatal morbidities such as eclampsia, puerperal endometritis, systemic infections, low birth weight, preterm delivery, and severe neonatal conditions [10][11][12]. Indeed, early adolescent pregnancy has been linked with an increased risk of HIV infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we observed that adolescent mothers were more likely to have an infant with the adverse birth outcome of preterm delivery, LBW, for preterm delivery in adolescent pregnancies, [6,13,15] which could be attributable to the maternal-fetal competition for nutrients that arises when pregnancy coincides with continuing or incomplete growth in adolescents. [20] Our study nds that adolescent mothers were more likely to deliver LBW babies is consistent with results from the Uganda Demographic Health Survey 2011.…”
Section: Discussionmentioning
confidence: 93%
“…[1, [6][7][8][9][10][11][12] However, few studies on birth outcomes among adolescents have been conducted in developing countries of sub-Saharan Africa, and available data is based on studies with small sample sizes. [13] We aimed to compare the occurrence of adverse birth outcomes (preterm birth, LBW, and ENND) and major external birth defects among adolescent mothers (12-19 years) to older mothers (20-34 years).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies and meta-analysis [22] detect a significant difference between pregnant adolescents and adult women, with up to 20% more preeclampsia events in pregnant adolescents than in adult women [23]; they actually report a greater risk of preeclampsia-eclapmsia in the group of adolescents between the ages of 13 and 16 when compared with women between the ages of 20 and 34, OR 2.97 (95%CI 1.62-5.42) [24], as well as lower frequencies of preeclampsia in adolescents (5%) vs. 1.5% in the adult group, and the difference was statistically significant, OR 3.66 (95%CI 1.67-7.72) [25].…”
Section: Preeclampsia-eclampsia In Adolescentsmentioning
confidence: 99%